If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -8x = 113 + -43x Solving 13 + -8x = 113 + -43x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '43x' to each side of the equation. 13 + -8x + 43x = 113 + -43x + 43x Combine like terms: -8x + 43x = 35x 13 + 35x = 113 + -43x + 43x Combine like terms: -43x + 43x = 0 13 + 35x = 113 + 0 13 + 35x = 113 Add '-13' to each side of the equation. 13 + -13 + 35x = 113 + -13 Combine like terms: 13 + -13 = 0 0 + 35x = 113 + -13 35x = 113 + -13 Combine like terms: 113 + -13 = 100 35x = 100 Divide each side by '35'. x = 2.857142857 Simplifying x = 2.857142857
| 5a+6b=7.15 | | 5k+2(k+1)=22 | | x^3+2x^2-35x= | | 1.8+3.16x=3.8 | | 102-66x=7x+24 | | 8x-2x+4(12x+y)= | | 2x^2+24x+72= | | x+18+3x=-28-3x-31 | | 0.5(12x-3.4)=-2(4x-1)+x | | -12+x=3-4+13 | | -x^2-13x-40= | | [x]=11 | | (n-6)*7=70 | | x^3-2x^2-35x= | | (11x^3-14x^2-17)+(-12x^3-16x^2+7x-40)= | | (n-5)*6=54 | | (n+5)*3=24 | | 4-20y=-4 | | 0.2(x-3)=4(0.2x-0.1) | | n-14=14 | | 45-6x=12+21 | | 4x^4-28x^3+40x^2= | | 9x+3=4x+7 | | 3x^2+33x+54= | | -x^2-15x-54= | | 106-9x=7x+22 | | n+35=52 | | -2x^3+12x^2+32x= | | n+15=17 | | -x^2+4x+2=0 | | 5[(2-3)-4]= | | 4y(7y-5)+12y= |